An Experimental Setup for Monitoring Distribution Transformer Health - Venkatakrishnan, Giri Rajanbabu; Rengaraj, Ramasubbu; Velumani, Arvindswamy (Distributed Generation & Alternative Energy Journal, 2021)
The Distribution transformers are the most expensive and important component which are used for transmission and distribution of electrical energy. It is imperative that the transformers function correctly without any faults, and should any faults occur, the same should be detected and corrected as soon as possible to prevent the failure of the power system to supply power. Health monitoring systems of distribution transformers are used to diagnose the distribution transformer and to deduce its working condition under the occurrence of incipient faults. This paper presents a model of a health monitoring system for distribution transformers in a laboratory environment. The proposed model ensures that faults do not disrupt the regular supply of power.